'A Peep at the Blacks'. A History of Tourism at Coranderrk Aboriginal Station, 1863-1924 - Clark, Ian (De Gruyter, 2016)
This book is concerned with the history of tourism at the Coranderrk Aboriginal Station at Healesville, northeast of Melbourne, which functioned as a government reserve from 1863 until its closure in 1924. At Coranderrk, Aboriginal mission interests and tourism intersected and the station became a 'showplace' of Aboriginal culture and the government policy of assimilation. The Aboriginal residents responded to tourist interest by staging cultural performances that involved boomerang throwing and traditional ways of lighting fires and by manufacturing and selling traditional artifacts. Whenever government policy impacted adversely on the Aboriginal community, the residents of Coranderrk took advantage of the opportunities offered to them by tourism to advance their political and cultural interests. This was particularly evident in the 1910s and 1920s when government policy moved to close the station.